A ARTE PERDIDA DE AMARRAR RAMINHOS DE FLORES - Gomes, Jennifer Pereira; Coutinho, Fernanda Maria Abreu (Revista de Letras, 2016)
Pelo senso comum contemporâneo Infância e Morte de-veriam ser apartadas uma da outra, pela preservação da própria criança, para que seus olhos sejam desviados do sofrimento. Deve, portanto, a criança ser poupada de qual-quer tipo de violência ou tristeza, como a doença e a morte. Nesses dois episódios geralmente emerge outra fi gura: a do médico. Em “Josefi na”, conto de Cecília Meireles, o encontro e velório da personagem homônima são relatados do ponto de vista de sua amiguinha. Junto à narrativa da dor da perda sentida pela criança narradora, a ausência do médico e de um tratamento adequado são as tônicas do conto. Palavras chave: Morte. Infância. Narrador. ABSTRACT By common sense and contemporary costum Childhood and Death should be separated from each other, for the pre-servation of the child, so that your eyes are diverted from suffering. Therefore, children should be spared any violence or sadness, as disease and death. In these two kinds of episode usually another fi gure emerges: the doctor’s. In “Josefi na” tale of Cecília Meireles, the meeting and the funeral of the eponymous character are counted from the point of view of his little friend. Along the narrative of the pain of loss felt by the child narrator, the absence of a physician and an appropriate treatment are keynotes of the story. Keywords: Death. Childhood. Narrator.